Peace, order and the glory of God: secular authority and the church in the thought of Luther and Melanchthon ; 1518 - 1559 - Estes, James Martin (Studies in medieval and Reformation traditions, 2005)
Emergency help from Christian brothers : Luther on secular authority and the church from 1520 through 1528 -- Peace, order, and good government : Melanchthon on secular authority and the church from 1519 through 1529 -- Anabaptists, Epicureans, and the glory of God : the emergence of Melanchthon's mature position, 1530-1535 -- Irenic Catholics, neutral princes, and godless bishops : the development of Melanchthon's thought from the De officio principum to the final edition of the Loci, 1539-1559 -- Faithful servants of God's Word : Luther on secular authority and the church from 1530 through 1545